Anopheles mosquitoes may drive invasion and transmission of Mayaro virus across geographically diverse regions. - Marco Brustolin; Sujit Pujhari; Cory A Henderson; Jason L Rasgon (Public Library of Science (PLoS), 2018)
The Togavirus (Alphavirus) Mayaro virus (MAYV) was initially described in 1954 from Mayaro County (Trinidad) and has been responsible for outbreaks in South America and the Caribbean. Imported MAYV cases are on the rise, leading to invasion concerns similar to Chikungunya and Zika viruses. Little is known about the range of mosquito species that are competent MAYV vectors. We tested vector competence of 2 MAYV genotypes in laboratory strains of six mosquito species (Aedes aegypti, Anopheles freeborni, An. gambiae, An. quadrimaculatus, An. stephensi, Culex quinquefasciatus). Ae. aegypti and Cx. quinquefasciatus were poor MAYV vectors, and had either poor or null infection and transmission rates at the tested viral challenge titers. In contrast, all Anopheles species were able to transmit MAYV, and 3 of the 4 species transmitted both genotypes. The Anopheles species tested are divergent and native to widely separated geographic regions (Africa, Asia, North America), suggesting that Anopheles may be important in the invasion and spread of MAYV across diverse regions of the world.